Versatile capabilities for growth in the context of transforming countries : Evidence from Polish manufacturing companies - Mitrega, Maciej; Siemieniako, Dariusz; Makkonen, Hannu; Kubacki, Krzysztof; Bresciani, Stefano (Elsevier, 2021)
This study follows the newest extension to the resource-based view of company strategy, namely the versatility approach, to explain how resource-restrained companies may expand on international markets. The focus is on dynamic capabilities in marketing and innovation functions, which are conceptualized as versatile resources in the context of companies from transforming countries. The paper develops a model in which these two capabilities are linked with market expansion and product expansion, whereby market expansion facilitates product expansion. The survey data is based on a sample of 590 Polish companies and provides empirical support for the hypothesized links. The trade-off effect related to the parallel development of marketing capabilities and innovation capabilities receives partial support. The results are compared with prior research in the field and the observed international expansion paths of companies from transforming countries. The study contributes to the limited knowledge on organic, resource-based modes of growth among companies from transitional economies that expand in asymmetrical power international markets. Overall, the study recommends investing in marketing and innovation capabilities as versatile resources that can help companies from transforming countries to expand in competitive international markets.
Keywords: Versatile dynamic capabilities; Marketing; Innovation; International market expansion; Transforming countries; Asymmetrical power markets; innovations; fi=Markkinointi|en=Marketing|